Two new species of the genus Eumenes Latreille, 1802 (Hymenoptera: Vespidae, Eumeninae) from Vietnam - Nguyen, Lien Thi Phuong (Zootaxa, 2016)
Seven species of the genus Eumenes Latreille, 1802, were recorded from Vietnam (Nguyen 2015), including two long-petiolate species (metasomal tergum 1 equal or more than 4 × as long as its maximum width): E. quadratus quadratus Smith and E. multipictus de Saussure, and five species with shorter petioles (metasomal tergum 1 less than 2.5 × as long as its maximum width): E. inconspicuus Smith, E. atrophicus (Fabricius), E. labiatus sinicus Giordani Soika, E. gibbosus Nguyen and E. rubronotatus Pérez. Two other long-petiolate species were were described from the Papuan region (Nugroho et al. 2010): E. batantanensis Nugroho and E. truncatus Nugroho. Two new species of the genus Eumenes with long-petiolate metasomal segment 1 are described from Vietnam. A key to all species occurring in Vietnam is also provided.